ASSESSING VOCABULARY IN THE LANGUAGE CLASSROOM - Siregar, Fitri Rayani (Department of English Education of STAIN Jurai Siwo Metro, 2015)
Abstract: Vocabulary is ultimate aspect in learning a language. A student who learns a foreign language should have a lot of vocabularies to developt some skills, namely speaking, writing, reading and listening. Also, the teacher needs a guide in assesing the tasks, examinition, and daily tasks.Â Keywords Vocabulary, Assessment